سلطات الضبطية القضائية بين الفعالية وحماية الحريات الفردية - أسامة شنوف (My University, 2023)
Summary: As a matter of justice and the establishment of the law, the legislator had to hire a judicial police apparatus to maintain the public security of society and defeat crime, and that by authorizing wide competencies that goes along with the current criminal development. In the context of research and investigation and gathering the evidence about the perpetrators of crimes especially the red-handed, members of the judicial police pursuit exceptional procedures, which affects the freedom of the suspects such as the procedure of arrest and detention for consideration. And in exchange of the authorities that the legislator give to the judicial police he circuit the suspect with procedural guarantees bound by criminal legitimacy, he also required the submitting of its members to the subordination and the management of a competent judicial authority represented by the Attorney general and Public prosecutor and the supervision of the indictment room, not to mention his determination of personal responsibility against the member who violates the established guarantees, and the invalidity of their illegal actions. .............................. ملخص: من باب العدالة وإرساء القانون كان لابد على المشرع تسخير جهاز الضبطية القضائية للحفاظ على الأمن العام للمجتمع ودحر الجريمة، وذلك بتخويله اختصاصات واسعة تتماشى والتطور الإجرامي الحاصل. في إطار البحث والتحري وجمع الاستدلالات حول مرتكبي الجرائم وخاصة المتلبس بها، يمارس أعضاء الضبطية القضائية إجراءات استثنائية، تمس بحرية المشتبه فيهم كإجراء القبض والتوقيف للنظر. وفي مقابل السلطات التي منحها المشرع للضبطية القضائية أحاط المشتبه فيه بضمانات إجرائية تقيدها بالشرعية الجنائية، كما ألزم خضوع أعضائها لتبعية وإدارة سلطة قضائية مختصة ممثلة في النائب العام ووكيل الجمهورية، وإلى رقابة غرفة الاتهام، ناهيك عن تقريره المسؤولية الشخصية في حق العضو المخالف للضمانات المقررة، وبطلان الأعمال غير المشروعة الصادرة منه. ............................ Résumé: Au nom de la justice et de l’établissement de la loi Le législateur devait mobiliser l’appareil de police judiciaire pour maintenir la sécurité générale de la société et vaincre la criminalité, en lui conférant de larges compétences en fonction de l’évolution criminelle en cours. Dans le cadre de la recherche, de l’enquête et de la collecte de preuves sur les auteurs d’infractions, en particulier celles en flagrant délit, les membres de la police judiciaire doivent prendre des mesures exceptionnelles portant atteinte à la liberté des suspects, telles que l’arrestation et la détention provisoire. En contrepartie des pouvoirs conférés par le législateur à la police judiciaire, le suspect était entouré de garanties procédurales qui les restreignaient à la légalité pénale et obligeait ses membres à être soumis à la subordination et à la gestion d’une autorité judiciaire compétente représentée par le procureur général et le ministère public, ainsi qu’au contrôle de la chambre d’accusation, sans parler de sa détermination de la responsabilité personnelle à l’encontre du membre qui viole les garanties établies, et de la nullité des actes illégaux qu’il a délivrés.